THE IMPACT OF TOURIST BEHAVIORS TOWARDS THE SOCIETY BEHAVIORAL CHANGE IN KARIMUNJAWA, INDONESIA - Putro, Sandy Suharto; Kosmaryandi, Nandi; Sunarminto, Tutut (Universitas Pendidikan Indonesia, 2020)
The increasing number of tourist visiting Taman Nasional Karimunjawa, Karimunjawa National Park, (herein referred to as TNKJ) has resulted in increased social interaction between tourists and local people. These conditions can affect the attitude of the community in Karimunjawa. The purpose of this study is to measure the influence of tourist behavior on changes in people's attitudes using a simple linear regression analysis method. The study was conducted in October-December 2019 with the research sample being the community of tourism service providers and non-tourism service providers. The hypothesis of this study is a negative influence of the perpetrators of tourists on the attitude of the people of TNKJ. The results of data analysis obtained (1) there is a significant influence of tourist behavior on the attitude of tourism service providers, as evidenced by the regression equation Y = 23,357 + 0.457X and the coefficient of determination of 22.6%. (2) there is no significant influence between the behavior of tourists on the attitude of the community not the provider of tourism services, as evidenced by the regression equation Y = 31,404 + 0.168X, but the t-test value is 1,947 1,994 and the coefficient of determination is 5.3%.